PENGARUH MEDIA PEMBELAJARAN PERMAINAN MONOPOLI TERHADAP KETERAMPILAN BERBICARA SISWA SMA N 5 KABUPATEN KEPULAUAN TANIMBAR - Naxa Elsina Luarmasse; Juliaans E R Marantika; Henderika Serpara (J-EDu: Journal - Erfolgreicher Deutschunterricht, 2021)
The influence of the “monopoly game” as learning media on the speaking ability of students of the SMA N 5 Tanimbar Islands District (KKT). The aim of this research is to describe whether there is an influence of the "monopoly game" as a learning media on the speaking ability of students of the SMA N 5 Tanimbar Islands District (KKT). The research was carried out at the SMA Negeri 5 Tanimbar Islands District (KKT). The sample of this research are students of class X MIPA 2. This research has two variables namely application of the monopoly game as a free variable and the speaking ability of the students as a bound variable. The research data were obtained through two tests. The first test was the pre-test, which was used in the classroom before using the learning media “Monopoly Game”, and the second was the post-test, which was used after the learning media “Monopoly Game” was used in the classroom. The data collected were processed by a t-test for dependent variable. The data show that t count = 10.08. If this result was compared to free value = (n = 21 and the significant level α = 0.05, t_tab = 1.72 was obtained. That means t_count = 10.08> t_tab = 1.72 [t_count is higher than t_tab This means that the use of the "monopoly game" as a learning medium has made a positive contribution to the speaking skills of the students. Based on this research, it can be suggested that the "monopoly game" can be used as a learning medium in the classroom in order to increase the speaking ability of the students to enhance